Open Heart Surgery in Patients with Rheumatic Mitral Valve Disease and Sickle Cell Disease, King Abdulaziz University Hospital: A 3 Years Experience - Husain H. Jabbad, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Patients with sickle cell trait or a disease who require cardiac surgery are at risk of a potentially fatal sickling crisis, which may be induced by hypothermia, hypoxia, acidosis, or low-flow states. Literature on the evaluation and specific management of these patients remains limited, and further studies are strongly recommended. This presents 3 years experience in King Abdulaziz University Hospital (2007-2009). A series of five patients with homozygous sickle cell disease and rheumatic heart disease underwent successful open heart surgery for cardiac valvular lesions, and evaluated in a retrospective nonrandom manner. Exchange transfusion was implemented in all cases, in addition to application measures to avoid/ or minimize vasoocclusive crisis. Two patients developed mild postoperative elevation of liver enzymes. One patient had perioperative low cardiac output and required inotrops and intra aortic balloon counter pulsation for one day, he required two weeks to recover from jaundice and elevated liver enzymes. All patients received anticoagulation for at least three months with no postoperative complications in their follow-up of 1-4 years. Heart valve surgery can be performed safely in patients with sickle cell disease with acceptable outcome, provided that the body environment during and after surgery is kept suitable and does not trigger vasospasm.